2023
DOI: 10.7717/peerj.14922
|View full text |Cite
|
Sign up to set email alerts
|

Association between coronary artery disease and incident cancer risk: a systematic review and meta-analysis of cohort studies

Abstract: Objective Coronary artery disease (CAD) and cancer are the two leading causes of death worldwide. Evidence suggests the existence of shared mechanisms for these two diseases. We aimed to conduct a systematic review and meta-analysis to investigateassociation between CAD and incident cancer risk. Methods We searched Cochrane, PubMed, and Embase from inception until October 20, 2021, without language restrictions. Observational cohort studies were used to investigate the association between CAD and incident ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In recent years, an increasing number of epidemiological and clinical studies have reported that patients with cardiovascular diseases are at higher risk of developing cancer [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. A very recent meta-analysis revealed an increased risk of incident cancer after a CAD event, particularly for lung and colorectal cancers, suggesting that detailed cancer surveillance programs should be implemented in patients with CAD to reduce cancer-related morbidity and mortality [ 1 ]. However, more research is warranted regarding the causes and risk factors of cancer in these patients [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, an increasing number of epidemiological and clinical studies have reported that patients with cardiovascular diseases are at higher risk of developing cancer [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. A very recent meta-analysis revealed an increased risk of incident cancer after a CAD event, particularly for lung and colorectal cancers, suggesting that detailed cancer surveillance programs should be implemented in patients with CAD to reduce cancer-related morbidity and mortality [ 1 ]. However, more research is warranted regarding the causes and risk factors of cancer in these patients [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…A very recent meta-analysis revealed an increased risk of incident cancer after a CAD event, particularly for lung and colorectal cancers, suggesting that detailed cancer surveillance programs should be implemented in patients with CAD to reduce cancer-related morbidity and mortality [ 1 ]. However, more research is warranted regarding the causes and risk factors of cancer in these patients [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations